Double free-flap for a bimalleolar defect of lower leg and ankle - Naren Shetty; Narendra S. Mashalkar; Sunder Raj Ellur; Karishma Kagodu (Indian Journal of Plastic Surgery)
Double free-flaps are necessary when tissue cover cannot be sufficed with a single flap. The other factors to be considered when using two free flaps for resurfacing of distal limb defects are the availability of more than one recipient vessel, the risk of distal limb ischaemia and the donor site morbidity of double flap harvest. If these factors are adequately addressed, double free-flaps can be safely executed for resurfacing distal limb defects with minimal morbidity. We report the simultaneous harvest and transfer of the anterolateral and anteromedial thigh flaps inset and vascularised as double free-flaps to resurface a large bimalleolar defect in a 14-year-old boy with no additional morbidity as compared to that of a single free tissue transfer.